'Unintended' audiences of alcohol advertising: exposure and drinking behaviors among Australian adolescents. (2nd January 2017) - Faulkner, Agatha; Azar, Denise; White, Victoria
Abstract: Purpose : To measure associations between exposure to alcohol advertising and drinking behaviors among secondary students in Victoria, Australia. Methods : Students aged 12–17 years completing a cross-sectional survey in 2011 ( n = 4, 413) indicated their exposure to alcohol advertising via multiple media channels. Students also indicated whether they had consumed alcohol in the past month and the number of alcoholic drinks consumed on each of the seven days preceding the survey. Students drinking five or more drinks on one of these seven days were classified as 'risky drinkers'. Logistic regression analyses examined associations between exposure to alcohol advertising media and alcohol consumption measures, controlling for student-level demographic variables. Results : Exposure to alcohol advertising was most common through television (58%), alcohol branded merchandise (42%), and the internet (39%). After controlling for other advertising exposure measures, weekly exposure to alcohol advertising via billboards/newspapers/magazines and ownership of at least one alcohol branded item was significantly associated with consuming alcohol in the past month and at risky levels. Conclusions : Findings show high exposure to alcohol advertising among Australian youth and associations with drinking behaviors, suggesting the need for increased regulation of alcohol advertising across traditional and non-traditional media.